Experimental assessment of social interactions in two species of the genus Teratoscincus (Gekkota) - Suchomelová, Petra; Jančúchová-Lásková, Jitka; Landová, Eva; Frynta, Daniel (Behavioural processes, 2015)
Social organization of many reptile species that are rare in the wild remains rather unexplored due to difficulties when setting experiments in the field. Behavioral analysis of standard social situations in laboratory conditions is considered an indirect method to reveal social behavior in the field. We studied two rare species of geckos, Teratoscincus scincus and Teratoscincus keyserlingii, inhabiting sand dunes of Uzbekistan and Eastern Iran. A series of experiments was carried out to quantify responses in social interactions among conspecific adults as well as reactions of these towards conspecific/heterospecific subadults and juveniles. We also assessed the effect of species and sex on recorded behavior. Finally, the reaction to threat stimuli simulating predator attack was analyzed. The species effect was recorded only in the response to a simulated predatory attack: T. scincus typically escaped whereas larger T. keyserlingii attacked the stimulus. In accordance with the sexual competition hypothesis, agonistic interactions were nearly exclusively confined to male-male encounters while females were tolerant to each other. Male-female encounters regularly resulted in mating attempts, which suggests that females are not strongly selective in choosing partners. Therefore, male aggression can be linked to mate guarding or territoriality. Adults' lack of interest in immature geckos may indicate generalized tolerance of adults towards young.
Keywords: Reproduction; Social interaction; Ecosystem; zvířata; Behavior, Animal; rozmnožování; sociální chování; Teratoscincus; Animals; Subadult; ještěři; agrese; Female; ekosystém; Male; Lizard; ženské pohlaví; teritorialita; Territoriality; mužské pohlaví; Species Specificity; chování zvířat; druhová specificita; Lizards; Offspring; Aggression; Agonistic interaction; Social Behavior